The rapid growth of the Chinese tourist industry, world heritage management in China - Szatmári, Sándor (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
Alongside with the fast and powerful development of the Chinese economy, the tourism industry has also went through a rapid growth, meanwhile China has become the world’s largest market of tourism in the recent years. According to several forecasts, the growth of tourism will maintain its measure. The reason’s of this tendency can be found in the inner processes of the Chinese society, including the growing number of well-off people in China. In the course of examining the Chinese tourism, it worth to examine in details the outbound, inbound and domestic tourism, as well as some questions of the development of tourism infrastructure, the methods, the aims and the focus of it. Within this framework the cooperation with world organizations in the fields of culture, heritage protection and economic cooperation is also quite a remarkable aspect. I would list here the UNESCO, and several UN Institutions, such as UNWTO (United Nations World Tourism Organization). The international tourism is founded on the legal framework and terminology of these organizations, especially regarding the concept and operation of world heritages. Because of the several thousands years of history of China, the heritage protection proves to be a highly useful, long-term investment, which significantly increases the attractiveness and value of tourism to the country. The Chinese tourism increases at all levels, the largest increase can be seen in outbound tourism, but the domestic and inbound tourism also increase at large scale.China becomes more open to the world, in Hungary we have the opportunityto get involved in this branch of industry and growth
Keywords: China; tourism; world heritage